Żeby sprzedać – trzeba dać O rynku i jego nierynkowych fundamentach - Michalski, Michał A. (Prakseologia, 2015)
The paper analyzes interdependence of the market sphere which functions according to the logic of contract, and the sphere of non-market activity within economy, where the logic of gift dominates as a paradigm. The purpose of the analysis is to present how the above concepts of societal exchange intertwine and complete each other within the socio-economic order. This is followed by the description of 'pre-market' economic paradigms (based on Karl Polanyi's contribution) such as reciprocity, redistribution and household. Special attention is paid to category of gift, which is presented as prior to contract and being a necessary condition of the former one. The purpose of the analysis undertaken in this paper is to show how understanding of the interaction discussed here is necessary for creating integrated vision of how socio-economic order functions and offers adequate perspective for formulating recommendations within social and economic policy. (English) "To Sell One Has to Give – of Market and Its Non-Market Foundations"
Sociology; Philosophy
Keywords: contract; economy; gift; gospodarka; kontrakt; market; rynek; socio-economic order; ład społeczno-gospodarczy

Bez zmian na „zielonej wyspie”? Kryzys ekonomiczny w polskich badaniach socjologicznych - Mrozowicki, Adam (Whither Green Island? The Global Economic crisis in Polish sociological research., 2014)
The article presents selected aspects of the discussion about the conditions and consequences of global economic crisis in Polish sociology. The author argues that the relatively limited debate on the nature of the current crisis can be explained by two factors. Firstly, it is the consequence of the dominance of modernisation paradigm in the analysis of the Polish social transformation as well as the marginalisation of two sociologies: critical labour sociology and economic sociology. Secondly, drawing on research carried out by the author on working- class life strategies in the 2000s, the limited debate is the outcome of social "normalisation" and "adaptation" to crisis experiences in the Polish society. Despite the symptoms of collective "demobilisation" in the face of successive crises, adaptation to crises has its social limits. The discourse of global economic crisis contributes to new forms of collective mobilisation in the sphere of work and politics regardless of the dominance of individualistic coping strategies inherited from the first decades of transformation. The "counter-movement" taking place in Poland is expressed in trade union radicalisation and mobilisation of radical-nationalist movements. Both processes are interpreted by the author with the reference to Karl Polanyi's work as the manifestations of self-defence of the society against the expansion of socially uncontrolled market mechanisms.
Sociology
Keywords: economic crisis; neoliberalism; sociology; the myth of the market

The Role of Consensus and Social Homogeneity in the Process of Building Capitalism in Post-communist Countries - Bieliński, Jacek (KONSENS I JEDNORODNOŚĆ SPOŁECZNA W PROCESIE BUDOWANIA KAPITALIZMU W KRAJACH POSTKOMUNISTYCZNYCH., 2006)
The focus of this article is on interpretation of progress of post-communist transformations. Classical approaches, particularly those of Max Weber and Karl Polanyi, rather than modern ones are used as basis for the empirical analysis. I argue that the success of capitalist project, both now and in the past, stems from the ability to work out a general consensus about the preceding economic order. I also claim that ethnic homogeneity can be a favorable factor for the post-communist transformation, especially in its initial phase. Moreover, unlike in fully developed market systems which are more stable and socially diverse, the success of market reforms in post-communist countries negatively correlates with their diversification. One of the main goals of this analysis is to describe empirically what this consensus refers to. Survey research shows that market reforms in former socialist block run more smoothly if the level of social consensus about key values, not necessarily liberal, is high. I analyzed values and attitudes defining the consensus and also the degree of their popularity among economic elites and non-elites. Data used in the analysis comes from the first edition of European Social Survey. (English)
Sociology
Keywords: WEBER; Max; 1864-1920; capitalism; economic sociology; elite; jednorodność; konsens społeczny; markets; post-communism; post-communist transformations; postcommunism; postcommunist societies; social consensus; social homogeneity; socjologia ekonomiczna; społeczna; transformacja postkomunistyczna